Rancang Bangun Sistem Monitoring Dan Proteksi Under Speed dan Over Speed Pada Motor Induksi 3 Phasa Berbasis Mikrokontroller - Syahrizal, Syahrizal; Novia Syamsir, Hendri; Gunawan, Arif; Sahar, Muzni; Aulia Ramadhani, Nabila; Yusuf Hasibuan, Muhammad (Politeknik Caltex Riau, 2025)
Three-phase induction motors are widely used in industrial applications due to their simple construction, high reliability, and relatively low maintenance cost. However, motor rotational speed is strongly dependent on the supply frequency, making the drive susceptible to speed deviations outside the allowable range. Both under-speed and over-speed conditions can lead to thermal stress, mechanical degradation, increased current draw, and premature motor failure. This study proposes a microcontroller-based monitoring and protection system designed to detect abnormal speed conditions in three-phase induction motors. A Hall effect sensor is utilized to measure the instantaneous rotational speed, while programmable speed limits are input through a keypad interface. The system automatically disconnects the motor supply once the detected speed exceeds the predefined threshold. The experimental results reveal that the system successfully identifies under-speed (e.g. 1391 rpm) and over-speed (e.g. 1509 rpm) conditions from predetermined set points (e.g., 1400 rpm and 1500 rpm), and automatically disconnect the motor with a fast response (2 seconds), confirming the effectiveness of the protection algorithm. This work contributes to low-cost and scalable protection solutions suitable for industrial motor applications, particularly for implementations requiring autonomous speed protection without high-end control equipment.